PENGARUH BUDAYA KERJA DAN KEPUASAAN KERJA TERHADAP KINERJA PEGAWAI DI KECAMATAN SUNGAI GERINGGING - Siti Fatimah; Aldri Frinaldi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This study aimed to determine, and identify whether there was a significant influence of work culture and job satisfaction on employee performance. This study was conducted in Sungai Geringging District. This study applied a quantitative method with associative approach. The sample in this study was a total sampling technique consisted of 74 employees. Data measurement was performed using a Likert scale. Data in this study were collected through questionnaire distributed to respondents. Data analysis was carried out by using classical assumption test and multiple linear regression. The results of this data analysis processing show that there is a positive influence of work culture on employee performance of Adjusted R Square is 0.070%, a significance value of 0.013 is smaller than 0.05. Job satisfaction has a significant effect on the employee performance of Adjusted R Square of 0.360%. Simultaneously work culture and job satisfaction have a significant effect on employee performance by 0.000 less than 0.05.